2003
DOI: 10.1128/aem.69.5.2444-2447.2003
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Prevalence of Escherichia coli O157 in Cattle Feces at Slaughter

Abstract: The concentration and prevalence of Escherichia coli O157 in cattle feces at the time of slaughter was studied over a 9-week period from May to July 2002. Fecal samples (n ‫؍‬ 589) were collected from the rectums of slaughtered cattle, and the animal-level prevalence rate was estimated to be 7.5% (95% confidence interval [CI], 5.4 to 9.6%) while the group prevalence was 40.4% (95% CI, 27.7 to 53.2%). Of the 44 infected animals detected, 9% were high shedders that contained E. coli O157 at concentrations of >10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
208
7
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(236 citation statements)
references
References 30 publications
(26 reference statements)
19
208
7
2
Order By: Relevance
“…This is contrary to other studies which noted an association between stx and eae gene in E. coli (Omisakin et al, 2003).…”
Section: Figcontrasting
confidence: 56%
“…This is contrary to other studies which noted an association between stx and eae gene in E. coli (Omisakin et al, 2003).…”
Section: Figcontrasting
confidence: 56%
“…Although studies to date have not assessed aEPEC prevalence, other studies of stx and O157:H7 dairy prevalence have shown both higher (72·7%, 11·1-32·3%) [15,18] and lower (1%) levels [10]. Importantly, high-shedding cattle have been hypothesized to influence herd EHEC propagation, and only one was observed in the current study [21,22]. To date, this is the first assessment of EHEC prevalence on dairies in the Rocky Mountain biome, so it is possible that lower shedding prevalence and measured outcomes may be inherent to the particular environment studied.…”
Section: Discussioncontrasting
confidence: 54%
“…Importantly, those animals shedding high quantities of the pathogen ('high-shedders'; >10 3 -10 4 c.f.u./g faeces) may account for the majority of O157 contamination within a herd, increasing animal-to-animal transmission and risk of food chain contamination [18,21,22]. When classifying cows based on O157 shedding magnitude vs. positive shedding alone, outcomes for risk factor analyses can become altered [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these illnesses have been linked to consumption of foods derived from or contaminated by animal products (4,21). Because pathogenic bacteria are commonly found as members of the gastrointestinal population of food animals (19,24,25), they can be introduced into the abattoir within the feces of cattle or attached to their hide (5,6,8,26).…”
mentioning
confidence: 99%